Trading Communities in the Roman World - Terpstra, Taco T. (Columbia studies in the classical tradition., 2013)
In Trading Communities, Taco Terpstra shows that long-distance trade in the Roman Empire was conducted through foreign trading communities living overseas, held together by ethnic and geographical identity.